Colonization of Octolasmis (Cirripedia) on the Crab Portunus Sanguinolentus (Brachyura: Portunidae): Impacts of the Parasitism of Diplothylacus Sinensis (Cirripedia: Rhizocephala). Issue 2 (1st March 2015) - Li, Heng-Xiang; Ma, Li-Sha; Yu, Xiu-Juan; Li, Lu; Yang, Chang-Ping; Yan, Yan
Abstract: Parasitism by rhizocephalans can cause morphological, physiological, and behavioral changes in their host crabs, thus potentially also affecting the structure and function of host populations in the benthic ecosystem. The dynamic variation in crab populations caused by rhizocephalans may affect the colonization of epibionts on the crabs, but there is little literature on host/parasite/epibiont relationships. This study investigated the patterns of colonization by the thecostracan barnacle Octolasmis on crabs parasitized by the rhizocephalan externae of Diplothylacus sinensis, in order to quantify the interaction of the epibionts and rhizocephalan. Two species of epibiont barnacles, Octolasmis bullata and O. warwickii, occurred on the host crab species Portunus sanguinolentus : O. bullata was found in the branchial chambers of all rhizocephalan-parasitized crabs, with an intensity of 74.6 ± 39.1 (mean ± SD) barnacles per host; O. warwickii was found attached to the outer surfaces of 34.6% of parasitized crabs, with an intensity of 49.3 ± 32.3 barnacles per host. Their patterns of colonization, including Octolasmis prevalence, intensity, and distribution, were not similar to those crabs unparasitized with the rhizocephalan externae in previous reports. Differences between the two groups of crabs were closely related to the parasitism by rhizocephalan externae of D. sinensis . Because the evidence in this study suggests that the parasite had arrested or reduced a series of host behaviors, such as molting, grooming, and burying, to protect the parasitization of rhizocephalan externae, although these behavioral patterns are natural antifouling mechanisms for the epibionts. As a result, Octolasmis could benefit from the behavioral changes of hosts in the rhizocephalan-crab association. Whereas, massive colonization of Octolasmis on rhizocephalan-parasitized crabs, especially long-term parasitized hosts, could pose a severe burden and lead to an increase in host mortality.